The sentry - Crais, Robert, 1953- (Orion, 2011)
After the nightmare of Hurricane Katrina, Dru Rayne and her uncle relocated to Los Angeles. Five years later, their struggling restaurant faces a different danger. When Joe Pike witnesses Dru's uncle beaten by a neighbourhood gang, he offers his own brand of protection, but neither Dru nor her uncle want his help. And neither do the federal agents mysteriously watching their store ... But Pike is falling for Dru and won't back away whether she wants his help or not. As the violence escalates, Joe discovers Dru and her uncle are not who they seem -and now a vengeful, murderous force from their past is catching up with them ...